Purification and Immobilization of Amylase Enzyme Produced from Local Isolate of Bacillus subtilis - Hamza, Haider Mussa (Sulaimani Journal for Pure and Applied Sciences, 2004)
Amylase enzyme produced from B. subtilis was purified by two main steps included precipitation with ammonium sulfate 40-80% saturation and gel filtration chromatography on Sephadex colunm (G-100). The obtained purification foid and recovery werc (67.92) and (43.9) % respectively. The ensyme was immobilized by enh'apment in calcium alginate beacls. The enzyme retained 53% af it's origiaal activity after a month of storage at 4oC. On the other hand, free enzyme lost its activity completely in less than 20 days. These results were revealed the possibiliry of using pwified amylase in indusky fields. Results also indicate the efficiency of immobilization technique by caicium alginate beads and preserving of the enzyme activity fbr a relatively long period of time.
Keywords: Amylase B subtiIis; Purification; Immobilization